Nalmefene for the management of alcohol dependence: review on its pharmacology, mechanism of action and meta-analysis on its clinical efficacy - Mann, Karl (European neuropsychopharmacology, 2016)
Nalmefene, a mu- and delta-opioid receptor (MOR, DOR) antagonist and a partial kappa-opioid receptor (KOR) agonist, is approved in the European Union and other countries for the reduction of alcohol consumption in alcohol dependent patients with a high drinking risk level according to WHO (“target population”). This review presents an overview of nalmefene׳s pharmacology, its mechanisms of action and a meta-analysis on its efficacy in reducing alcohol consumption. The review was based on a systematic search of the literature. Random effects meta-analyses were performed on published and unpublished trials directed at drinking reduction using the changes in heavy drinking days (HDDs) and daily total alcohol consumption (TAC) from baseline to the primary endpoint. For each included study and each dose, Hedges’ g was used as an unbiased estimator of the standardised mean differences between nalmefene and placebo. Preclinical data suggests that nalmefene counters alcohol-induced dysregulations of the MOR/endorphine and the KOR/dynorphin system. Evidence further suggests that reduced alcohol consumption is an effective treatment strategy that appeals to patients not ready for abstinence. Finally, meta-analyses confirmed the efficacy of 20mg nalmefene for reducing HDDs in the ITT population (Hedge׳s g=−0.20; 95% CI −0.30 to −0.09) and the target population (Hedge׳s g=−0.33; 95% CI −0.48 to −0.18). Similar results were seen for TAC. Several meta-analyses, including this new meta-analysis, support nalmefene׳s efficacy in reducing alcohol consumption. In conclusion, because it does not require abstinence, this treatment has the potential to motivate more patients for treatment and thus helps to address a major public health concern.
Gesehen am 28.03.2019
Available online 12 November 2016